Cellular Mechanisms of Melatonin: Insight from Neurodegenerative Diseases - Chen, Dongmei (Biomolecules, 2020)
Neurodegenerative diseases are the second most common cause of death and characterized by progressive impairments in movement or mental functioning in the central or peripheral nervous system. The prevention of neurodegenerative disorders has become an emerging public health challenge for our society. Melatonin, a pineal hormone, has various physiological functions in the brain, including regulating circadian rhythms, clearing free radicals, inhibiting biomolecular oxidation, and suppressing neuroinflammation. Cumulative evidence indicates that melatonin has a wide range of neuroprotective roles by regulating pathophysiological mechanisms and signaling pathways. Moreover, melatonin levels are decreased in patients with neurodegenerative diseases. In this review, we summarize current knowledge on the regulation, molecular mechanisms and biological functions of melatonin in neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, vascular dementia and multiple sclerosis. We also discuss the clinical application of melatonin in neurodegenerative disorders. This information will lead to a better understanding of the regulation of melatonin in the brain and provide therapeutic options for the treatment of various neurodegenerative diseases.